CO2 reduction to formic acid at low overpotential on BDD electrodes modified with nanostructured CeO2. Issue 30 (12th July 2019) - Verlato, Enrico; Barison, Simona; Einaga, Yasuaki; Fasolin, Stefano; Musiani, Marco; Nasi, Lucia; Natsui, Keisuke; Paolucci, Francesco; Valenti, Giovanni
Abstract : Nanostructured CeO2 /BDD electrodes produce formic acid with good faradaic efficiency at very low overpotential (>40% at η ≈ 40 mV). Abstract : Ceria was deposited onto boron doped polycrystalline diamond (BDD) cathodes, through electrochemically induced precipitation from nitrate-based solutions. The deposits were characterized using SEM-EDS, HRTEM, XRD and XPS. The morphology, thickness and composition of ceria films, which besides CeO2 contained Ce(OH)3 when prepared at very negative potential, were controlled by tuning the deposition parameters. Thin Ce(OH)3 -free ceria films allowed CO2 electrochemical reduction at overpotentials below 50 mV, yielding formic acid with faradaic yield higher than 40% and stable performance for many hours. Ceria seemed to act as a co-catalyst that activated CO2 for reduction at the H-terminated BDD surface, because comparable results were not obtained with ceria-coated glassy carbon electrodes.